Can self-efficacy have a role in learning interest - Azzah Kurnia Dewi; Sri Maria Puji Lestari; Vira Sandayanti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Self-efficacy is one of the important things that must be possessed by all students, including medical students. Self-efficacy is an individual's belief in their ability to perform the task or action required to achieve a certain result. Self-efficacy is an important variable for students to evaluate because with self-efficacy people can perform certain tasks properly and correctly. One of the influential factors in self-efficacy is interest in learning. Interest in learning is a feeling of interest and pleasure that causes a desire to establish a more positive relationship, characterized by feelings of pleasure without a relationship, studying references about school subjects with pleasure, sincerely carrying out activities without any internal or external coercion from the individual. To determine the relationship between learning interest and self-efficacy in undergraduate students of the Faculty of Medicine, Malahayati University. Based on the research results, it was found that a sample of 228 students with a low level of interest in learning was not found and students who had the most interest in learning were in the category of high learning interest totaling 145 students (63.6%), and students, then for the highest level of self-efficacy in the high category there were 140 students (61.4%). Statistical analysis using the Spearman test showed a p=value of <0.000 with a correlation test of 0.942. There is a significant relationship between interest in learning and self-efficacy in students of the Faculty of Medicine at the Bachelor Stage of Malahayati University. Interest in learning affects self-efficacy by 92.3%.Efikasi diri merupakan salah satu hal yang penting yang harus dimiliki oleh semua mahasiswa termasuk mahasiswa kedokteran. Efikasi diri adalah keyakinan individu dalam kemampuan mereka untuk melakukan tugas atau tindakan yang diperlukan untuk mencapai hasil tertentu. Efikasi diri merupakan variabel penting bagi mahasiswa untuk evaluasi karena dengan rasa percaya diri seseorang dapat melakukan tugas-tugas tertentu dengan baik dan benar. Salah satu faktor yang berpengaruh dalam efikasi diri adalah minat belajar. Minat belajar adalah perasaan tertarik dan senang yang menyebabkan keinginan untuk menjalin hubungan yang lebih positif, ditandai dengan perasaan senang tanpa adanya hubungan, mempelajari referensi tentang mata pelajaran sekolah dengan perasaan senang, dengan ikhlas melakukan kegiatan tanpa ada paksaan internal maupun eksternal dari individu tersebut. Untuk mengetahui hubungan minat belajar dengan tingkat efikasi diri pada mahasiswa Fakultas Kedokteran Tahap Sarjana Universitas Malahayati. Berdasarkan hasil penelitian didapatkan sampel sebanyak 228 mahasiswa dengan tingkat minat belajar rendah tidak ditemukan dan mahasiswa yang memiliki minat belajar terbanyak adalah dalam kategori minat belajar tinggi berjumlah 145 mahasiswa (63,6%), dan mahasiswa, kemudian untuk tingkat efikasi diri terbanyak dalam kategori tinggi berjumlah 140 mahasiswa (61,4%). Analisis statistik menggunakan uji spearman menunjukkan p=value sebesar <0,000 dengan uji korelasi sebesar 0,942. Terdapat hubungan bermakna antara minat belajar dengan efikasi diri pada Mahasiswa Fakultas X.